Reliability Research of the Gear of Variable Displacement Gear Type Oil Pump - Liu Xubing; Wang Xiaolan; Liu Xintian; Wang Yansong (Jixie chuandong)
The fatigue reliability of gear play a important role in the service life of the variable displacement gear type oil pump.Based on multi-body dynamic theory and variable displacement gear type oil pump working principle,the virtual prototype model is established.The validity of model is verified by experiment,and the dynamic meshing force between gears is obtained by simulation.According to the gear contact fatigue reliability calculation model,the reliability of the gear is calculated in representative condition.The results of reliability have project value and can provide theoretical basis for the optimization design.